Prinsip Dasar Kualitas Seorang Pengajar Kristen di Gereja Menurut 1 Timotius 4:6-8 - Baskoro, Paulus Kunto; Matulessy, Yosua Yosia (Jurnal Teologi dan Pelayanan Kerusso, 2024)
Since the beginning, Christian education has come from the church, the church has become the center or center of Christian religious education so that Christian education in the church should be taken seriously, quality and quality should be improved. The church in the modern era needs qualified teaching staff. The quality of a teacher can be reviewed in the letter 1 Timothy 4:6-8 which is the topic of discussion in this article. By using a qualitative method and an interpretive approach (interpretative design) the author observes the text of 1 Timothy 4:6-8 with the principle of hermeneutic interpretation to reveal and explain the basic principles regarding the quality of Christian teachers in the church. The results found are that the quality of Christian teachers must have knowledge of the scriptures (intellectual) as a basis for teaching and have a good spiritual life (spiritual).